A Social Marketing Intervention to Prevent Drowning Among Inner-City Youth. Issue 2 (March 2018) - Glassman, Tavis J.; Castor, Tom; Karmakar, Monita; Blavos, Alexis; Dagenhard, Paige; Domigan, Julianne; Sweeney, Erin; Diehr, Aaron; Kucharewski, Ruthie
Background . Water-related injuries and fatalities pose serious public health issues, especially to African American youth, a demographic group that drowns at disproportionately high rates. Aim. The purpose of this study was to determine if a social marketing intervention targeting the parents and guardians of inner-city youth (U.S. Midwest) could positively influence their perceptions concerning water safety. Method. Researchers employed a quasi-experimental design using matched pairs to evaluate the intervention. Participants consisted of parents who enrolled their children in a six-session survival-swimming course. Guided by the Health Belief Model, the researchers disseminated six prevention messages using six different channels (brochure, e-mail, SMS text message, postcard, Facebook, and window cling). Results . The findings from a two-way analysis of covariance revealed that treatment group participants' knowledge and perceptions of water-related threat all changed favorably. Additionally, all participants planned to reenroll their children in swim lessons. Discussion. A social marketing campaign using the Health Belief Model improved inner-city parents' knowledge regarding water safety and enhanced their self-efficacy. Conclusion . This study provides practitioners with feasible strategies (prevention messages) to supplement swim lessons, with the ultimate goal of preventing drowning among at-risk youth.